2018
DOI: 10.1002/rth2.12122
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic nucleotide‐dependent inhibitory signaling interweaves with activating pathways to determine platelet responses

Abstract: Platelets are regulated by extracellular cues that impact on intracellular signaling. The endothelium releases prostacyclin and nitric oxide which stimulate the synthesis of cyclic nucleotides cAMP and cGMP leading to platelet inhibition. Other inhibitory mechanisms involve immunoreceptor tyrosine‐based inhibition motif‐containing receptors, intracellular receptors and receptor desensitization. Inhibitory cyclic nucleotide pathways are traditionally thought to represent a passive background system keeping plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 119 publications
(234 reference statements)
0
41
0
Order By: Relevance
“…Subsequently, in our analysis of the iloprost/cAMP-stimulated phosphoproteome of human platelets, more than 130 cAMP/PKA regulated phosphoproteins were detected including ENSA (phosphorylated at S109) and ARPP19 (at S104) [35]. Platelets are strongly inhibited by both cAMP-and cGMP-elevating agents mediated by the corresponding cAMP-and cGMP-dependent protein kinases (PKA/PKG), which have overlapping specificity [18,19]. Therefore, we investigated the effect of the cGMP/PKG-pathway on ENSA/ARPP19 phosphorylation using various NO-donors [S-nitrosocysteine (SNC), sodium-nitroprusside (SNP), diethylamine NONOate (DEA-NO)] and the soluble guanylyl cyclase (sGC)-stimulator riociguat in comparison to the iloprost (cAMP) pathway, using vasodilator-stimulated phosphoprotein (VASP) as established PKA/PKG substrate and marker.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, in our analysis of the iloprost/cAMP-stimulated phosphoproteome of human platelets, more than 130 cAMP/PKA regulated phosphoproteins were detected including ENSA (phosphorylated at S109) and ARPP19 (at S104) [35]. Platelets are strongly inhibited by both cAMP-and cGMP-elevating agents mediated by the corresponding cAMP-and cGMP-dependent protein kinases (PKA/PKG), which have overlapping specificity [18,19]. Therefore, we investigated the effect of the cGMP/PKG-pathway on ENSA/ARPP19 phosphorylation using various NO-donors [S-nitrosocysteine (SNC), sodium-nitroprusside (SNP), diethylamine NONOate (DEA-NO)] and the soluble guanylyl cyclase (sGC)-stimulator riociguat in comparison to the iloprost (cAMP) pathway, using vasodilator-stimulated phosphoprotein (VASP) as established PKA/PKG substrate and marker.…”
Section: Resultsmentioning
confidence: 99%
“…We observed that cAMP-and cyclic guanosine monophosphate (cGMP)-elevating platelet inhibitors strongly inhibited GPIbα-/GPVI-mediated platelet activation but enhanced the initial Syk activation [28]. These phosphoproteomic and functional approaches suggest that there is a network of interacting protein kinases at the level of Syk in platelets [29,30].…”
Section: Introductionmentioning
confidence: 95%
“…This agonist-induced Syk S297 phosphorylation is also inhibited by the cAMP/PKA pathway, which is known to strongly inhibit receptor-stimulated Ca2 + responses and PKC activation [30,36,37].…”
mentioning
confidence: 99%
“…These factors contribute to the regulation of platelet function and haemostasis, by maintaining platelets in their inactive state. [1][2][3] PGI 2 binds to a Gs-coupled receptor, thus stimulating cAMP synthesis by adenylate cyclase. NO diffuses through the cellular membrane and activates soluble guanylate cyclase to produce cGMP.…”
Section: Introductionmentioning
confidence: 99%